Invertebrate richness, diversity and hatching patterns from a semi-arid pool in peninsular India using field sampling and sediment re-hydration - Ghodke, Neha Kiran; Padhye, Sameer Mukund; Vanjare, Chitra Avinash; Katke, Prashant Manohar; Vanjare, Avinash Isaac (Journal of arid environments, 2023)
Effective methods for finding the true species richness are necessary for biodiversity research. Such assessments are especially difficult for short-lived freshwater invertebrates found in arid and semi-arid temporary habitats. However, many of these animals produce “resting eggs” that remain viable for a long time and hatch when the habitats refill with water. This aspect can be used to assess the true species richness of these assemblages. We performed a simple, fast, cost-effective, and reliable method of laboratory sediment rehydration along with standard field sampling to understand the richness, diversity and hatching patterns of invertebrates like rotifers, cladocerans, copepods and ostracods and large branchiopods from a temporary pool located in the semi-arid part of peninsular India. Twenty-two rotifers, 5 large branchiopods and 6 micro-crustaceans were found in the study of which 4 species were only found from the rehydrated sediment. Variation in the species composition was higher in the field samples than the lab ones. Field and laboratory species communities were distinct from each other. Species community comparison with a similar habitat nearly 150 km away showed a dissimilarity of 0.70 between the two. Contrasting environmental conditions between the field and lab combined with temporal variation in the hatching patterns of species might explain the dissimilarities seen in the fauna. We propose that the sediment rehydration method along with the field sampling can be used to reveal the true species richness of the local temporary water bodies. •Thirty-three invertebrates were obtained from field and sediment rehydration studies.•Four species were exclusively seen in sediment rehydrated samples.•Sediment rehydration is a fast, easy, and cost-effective method to study biodiversity.•Field and rehydration method together revealed true species richness of the pool.